Human Bone Marrow Mesenchymal Stromal/Stem Cells Regulate the Proinflammatory Response of Monocytes and Myeloid Dendritic Cells from Patients with Rheumatoid Arthritis - Paula Laranjeira; Mónia Pedrosa; Cátia Duarte; Susana Pedreiro; Brígida Antunes; Tânia Ribeiro; Francisco dos Santos; António Martinho; Margarida Fardilha; M. Rosário Domingues; Manuel Abecasis; José António Pereira da Silva; et al. (MDPI AG, 2022)
Rheumatoid arthritis (RA) is a disabling autoimmune disease whose treatment is ineffective for one-third of patients. Thus, the immunomodulatory potential of mesenchymal stromal/stem cells (MSCs) makes MSC-based therapy a promising approach to RA. This study aimed to explore the immunomodulatory action of human bone marrow (BM)-MSCs on myeloid dendritic cells (mDCs) and monocytes, especially on cytokines/chemokines involved in RA physiopathology. For that, LPS plus IFNγ-stimulated peripheral blood mononuclear cells from RA patients (n = 12) and healthy individuals (n = 6) were co-cultured with allogeneic BM-MSCs. TNF-α, CD83, CCR7 and MIP-1β protein levels were assessed in mDCs, classical, intermediate, and non-classical monocytes. mRNA expression of other cytokines/chemokines was also evaluated. BM-MSCs effectively reduced TNF-α, CD83, CCR7 and MIP-1β protein levels in mDCs and all monocyte subsets, in RA patients. The inhibition of TNF-α production was mainly achieved by the reduction of the percentage of cellsproducing this cytokine. BM-MSCs exhibited a remarkable suppressive action over antigen-presenting cells from RA patients, potentially affecting their ability to stimulate the immune adaptive response at different levels, by hampering their migration to the lymph node and the production of proinflammatory cytokines and chemokines. Accordingly, MSC-based therapies can be a valuable approach for RA treatment, especially for non-responder patients.